2020
DOI: 10.18805/lr-4337
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Quality Attributes and Powdery Mildew Severity in Garden Pea (Pisum sativum Var. Hortense L.) under Sub Temperate Conditions of North-Western Himalayas

Abstract: Background: The choice of appropriate breeding method for improvement of traits depends largely on gene action. Hence, an understanding of the inheritance of quantitative traits is essential to develop an efficient breeding strategy.Methods: Twelve generations of three inter-varietal crosses involving four diverse parents of garden pea were studied for biochemical traits and powdery mildew disease severity to analyze the nature of gene effects by using generation mean anaylsis.Result: Duplicate type of epistas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…However, there is need for further evaluation of more numbers of lines against powdery mildew to find more resistant materials. The findings of screening is similar to Tiwari et al (1997); Singh et al (1988); Pandey et al (1999); Shiwani and Sharma (2022). Similarly, Davidson et al (2004) screened for 88 lines, of which 19 lines were showed powdery mildew resistance.…”
Section: Resultssupporting
confidence: 81%
“…However, there is need for further evaluation of more numbers of lines against powdery mildew to find more resistant materials. The findings of screening is similar to Tiwari et al (1997); Singh et al (1988); Pandey et al (1999); Shiwani and Sharma (2022). Similarly, Davidson et al (2004) screened for 88 lines, of which 19 lines were showed powdery mildew resistance.…”
Section: Resultssupporting
confidence: 81%